Analisis Kesalahan Ejaan Bahasa Indonesia dalam Surat Resmi Kantor Dinas Kehutanan Provinsi Kalimantan Timur Tahun 2018/2019 - Zakia, Izza; Hudiyono, Yusak; Ahmad, M. Rusydi (Universitas Mulawarman, 2020)
This study aims to describe Indonesian spelling errors in official letters issued by the General Sub-Section of the East Kalimantan Provincial Forestry Service Office. This study uses a descriptive qualitative research approach by collecting, compiling and presenting data. The technique used by the writer in this research is observation, documentation, listening technique and note-taking technique. The author analyzes or finds out spelling errors by listening to the letters one by one, then notes and counts spelling errors as a whole. Based on the results of the research that the author examined on official letters, there were still spelling errors in Indonesian which focused on errors: 1) writing the use of letters, 2) writing punctuation marks and 3) writing words. From this description, the author concludes that in writing the Indonesian spelling in an official letter in the General Sub-Section of the East Kalimantan Provincial Forestry Service Office, there are still some errors in the writing, as evidenced by the results of research conducted by the author.